2004
DOI: 10.1159/000080387
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Examination of Anxiety Persistence and Its Relationship to Cardiac Symptoms and Recurrent Cardiac Events

Abstract: Background: The current study builds on previous research demonstrating a link between anxiety and inhospital recurrent ischemic and arrhythmic events, by examining the effects of persistent anxiety on recurrent events 1 year later. Methods: 913 patients with unstable angina (UA) and myocardial infarction (MI) from 12 coronary care units were recruited, and follow-up data were collected at 6 and 12 months after the event. Measures included cardiac symptomatology, healthcare utilization, the anxiety subscale of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
153
0
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(169 citation statements)
references
References 23 publications
9
153
0
7
Order By: Relevance
“…As outlined previously, anxiety and depression are both prognostic risk factors for CVD, highlighting the need to be able to assess these disorders via the HADS (49)(50)(51)(52)(53)(54)(55). Having the ability to quantify mutually exclusive levels of anxiety and depression is an integral component of assessment when the prognoses are specifically predicted by one or the other disorder; however, in the case of CVD, both anxiety and depression are prognostic risk factors, negating the need to differentiate between these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…As outlined previously, anxiety and depression are both prognostic risk factors for CVD, highlighting the need to be able to assess these disorders via the HADS (49)(50)(51)(52)(53)(54)(55). Having the ability to quantify mutually exclusive levels of anxiety and depression is an integral component of assessment when the prognoses are specifically predicted by one or the other disorder; however, in the case of CVD, both anxiety and depression are prognostic risk factors, negating the need to differentiate between these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Several large studies have noted a relationship between phobic anxiety and sudden cardiac death (41,42). In addition, Grace et al (18) reported nonphobic anxiety to have a negative effect on self-reported recurrent cardiac events following an ischemic coronary event. However, data linking the various forms of anxiety to CAD are relatively rare and more work is needed.…”
Section: Discussionmentioning
confidence: 99%
“…The BDI is a reliable and wellvalidated measure of depressive symptomatology (15,16) and is the most widely used self-report measure of depression. BDI scores 10 or higher are indicative of at least mild to moderate symptoms of depression and have been associated with poor prognosis in MI patients (4,6,17,18).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite their high prevalence and serious impact, mood and anxiety symptoms go unrecognized and untreated in most ACS patients and such symptoms (rather than being transient reactions to ACS) persist for months and beyond. The mechanisms by which depression and anxiety are linked to these negative medical outcomes are likely a combination of the effects of these conditions on inflammation, catecholamine's, heart rate variability, and endothelial function, along with effects on health promoting behavior [19][20][21][22][23][24].…”
Section: Shetty Et Almentioning
confidence: 99%